PERCEIVED SOCIAL SUPPORT AND AFFECTIVE DISORDERS: A COMPARISON OF INDIVIDUALS WITH DEPRESSION AND BIPOLAR DISORDER - Piotr Łapiński; Jan Bombuy Gimenez; Maja Ćwiek; Ignacy Sterliński; Aleks Świderek (International Journal of Innovative Technologies in Social Science, 2025)
Background: Research on social functioning difficulties in individuals with bipolar disorder has produced inconsistent findings, ranging from significant social impairments to no differences or even superior outcomes compared to patients with depression. Current literature is limited by methodological constraints including use of non-validated self-report measures, lack of analysis of specific support sources, and absence of appropriate clinical comparison groups. These contradictory results necessitate investigation of alternative variables that may explain social support variations in affective disorders, which is crucial for developing targeted psychosocial interventions for bipolar disorder populations. Methods: A quasi-experimental study recruited 89 participants (52 bipolar disorder, 37 depression) from online support groups across Polish, English, and Spanish-speaking populations. Perceived social support was measured using the Multidimensional Scale of Perceived Social Support (MSPSS). ANCOVA models controlled for age, gender, and psychiatric comorbidity. Results: No significant differences emerged between diagnostic groups after controlling for covariates (p > .05). However, age was negatively correlated with global support (p = .021), friends support (r = −.28, p < .007), and significant other support (r = −.23, p = .028), while family support remained stable (r = −.06, p = .555). Both groups scored substantially below Polish population norms with large effect sizes (bipolar disorder: d = −1.11; depression: d = −1.29; p < .001). Conclusions: Age, rather than diagnostic category, predicts perceived social support decline in affective disorders. Both groups demonstrate clinically meaningful social support deficits, suggesting common vulnerabilities requiring targeted interventions across affective disorder spectrum.